Optimization and characterization of azadirachta indica loaded transdermal patches preparation - Ali, Arshad; Singh, Maneesh Kumar; Ul Islam, Mojahid (International journal of health sciences, 2022)
The Transdermal patches of Neem (methanolic extract) (F1, F2, F3, F4 and F5) were successfully prepared by solvent casting method using HPMC K100M in 1:1.1:2, 1:2, 1:3 and 1:4 ratios. The FTIR studies did not reveal any significant drug interactions. The prepared patches showed good results for physicochemical evaluations, in-vitro diffusion studies and anti-bacterial screening studies. On comparing major in evaluation criteria, formulation F4 was selected as best formulation. The release kinetics of all the patches showed zero-order kinetics and followed non-Fickian diffusion mechanism. The anti-bacterial screening study showed good anti-bacterial activity against Bascillus subtilis and Pseudomonas aeruginosa and zone of Inhibition (ZOI) was compared against standard anti-biotic drugs. It can be concluded from this project work that, from this novel approach, herbal drugs in the extract/ oil of the product can transformed into Transdermal Patches for the bio active properties pertaining to a stable formulation in accordance with its appropriate formulations. Although Transdermal systems provide a promising route of delivery for new age drugs, conventional and new dosage forms are equally essential for other drugs to increase their therapeutic efficacy.